Pembaharuan Nikah Bagi Masyarakat Madura Ditinjau Dari Maslahah (Studi Kasus di Kelurahan Parit Lalang Kota Pangkalpinang) - Mahbubah, Mahbubah; Suhendra, Darmiko; Wildan, Mursyidul (Fakultas Syariah dan Ekonomi Islam, IAIN Syaikh Abdurrahman Siddik, Bangka Belitung, 2024)
Marriage renewal is a belief carried out by the Madurese people as a way to strengthen household relationships from all unwanted things such as divorce. So the implementation of the Marriage Renewal that takes place in Parit Lalang Village, Pangkalpinang City has different views regarding its implementation for the surrounding community and not all of the Madurese people carry out the Marriage Renewal in Parit Lalang Village, only some of the Madurese people still have this belief. So this phenomenon encourages researchers to conduct research to look for the factors behind the Marriage Renewal process and will review Maslahah's implementation process.This research is qualitative research using a field approach (Field Research). The source of this research is primary data obtained from observations and interviews with couples who have carried out marriage renewal as well as religious figures who usually accompany the marriage renewal process to find out the reasons and consequences that occur after the marriage renewal process takes place. And equipped with secondary data as support.Based on the research results, the implementation of Marriage Renewal occurred because of household problems, namely the economy was not running smoothly, resulting in frequent arguments, loss of feelings of love and affection towards the partner, carried out as a form of commemorating the wedding day and so on. Then, regarding the marriage renewal process, there are couples who carry out marriage renewal more than once. So this is contrary to Islamic law, because the implementation that occurs in the field of the process is carried out in accordance with the pillars and conditions of marriage in general and in this process also provides a new dowry to the wife. So the law of marriage renewal which uses a new dowry in the marriage contract is the same as the husband admitting that the divorce will occur between them. If it is related to the Ushul Fiqh method, Maslahah is included in the Maslahah Mulgoh group, because it is contrary to the text, even though this action creates benefits for their household relations.